In Situ Regeneration of Copper-Coated Gas Diffusion Electrodes for Electroreduction of CO2 to Ethylene - Bisztyga-Szklarz, Magdalena; Mech, Krzysztof; Marzec, Mateusz; Kalendarev, Robert; Szaciłowski, Konrad (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
A key challenge for carbon dioxide reduction on Cu-based catalysts is its low faradic efficiency (FE) and selectivity towards higher-value products, e.g., ethylene. The main factor limiting the possibilities of long-term applications of Cu-based gas diffusion electrodes (GDE) is a relatively fast drop in the catalytic activity of copper layers. One of the solutions to the catalyst stability problem may be an in situ reconstruction of the catalyst during the process. It was observed that the addition of a small amount of copper lactate to the electrolyte results in increased Faradaic efficiency for ethylene formation. Moreover, the addition of copper lactate increases the lifetime of the catalytic layer ca. two times and stabilizes the Faradaic efficiency of the electroreduction of CO2 to ethylene at ca. 30%. It can be concluded that in situ deposition of copper through reduction of copper lactate complexes present in the electrolyte provides new, stable, and selective active sites, promoting the reduction of CO2 to ethylene. © 2021 by the authors. Licensee MDPI, Basel, Switzerland. Published under the CC BY 4.0 license.--//-- This is the published version of the article Bisztyga-Szklarz, M.; Mech, K.; Marzec, M.; Kalendarev, R.; Szaciłowski, K. In Situ Regeneration of Copper-Coated Gas Diffusion Electrodes for Electroreduction of CO2 to Ethylene. Materials 2021, 14, 3171. https://doi.org/10.3390/ma14123171.
This research was funded by the European Union’s Horizon 2020 research and innovation program under grant agreement No 768789 as well as by the Polish National Centre of Science under grant no 2017/26/D/ST8/00508. The Institute of Solid State Physics, University of Latvia, as a center of excellence, has received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement no. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES; Carbon dioxide; Copper catalysts; Copper complexes; Electrocatalysis; Ethylene; GDE